Single cell RNA transcriptome response to fentanyl use in persons with hepatitis C virus infection - Roskin, Krishna M.; Meeds, Heidi L.; Madhuravasal Krishnan, Janani; Juhascik, Matthew; Cafardi, John M.; Brown, Jennifer L.; Freiermuth, Caroline; Lyons, Michael S.; Sherman, Kenneth E.; Blackard, Jason T. (Frontiers in Virology, 2025)
IntroductionThe US has experienced a major drug epidemic in recent years, attributed in large part to synthetic opioids such as fentanyl. Here, we evaluated how recreational / non-prescribed fentanyl use in persons living with HCV infection impacted gene expression profiles in the peripheral blood.MethodsWhole blood was collected from 11 individuals, including 4 HCV-negative healthy controls, 4 HCV-positive individuals with current fentanyl use, and 3 HCV-positive individuals with no current fentanyl / no opioid use.ResultsThe median HCV RNA level was 5.6 log10 copies/mL. Cell frequencies were not different by fentanyl status except for non-CD4+, non-CD8+ T cells (higher for fentanyl use; p = 0.052). When comparing HCV-positive persons with / without fentanyl detected in their blood, 106 differentially expressed genes (DEGs) were identified, including 11 in CD4+ T lymphocytes, 46 in CD8+ T lymphocytes, 5 in monocytes, 13 in B lymphocytes (excluding plasmablasts), 24 in plasmablasts, 2 in dendritic cells, and 13 in NK cells. Seven DEGs – DHRS4L2, GZMA, H1-3, HLA-C, ISG15, PARP8, PRKX – were shared across multiple cell types, with the majority being involved in host defenses against viruses. Enrichment analysis of differentially expressed genes identified genes involved in multiple cellular processes and phenotypes. Expression of the HCV entry factor CD81 was high in PBMCs; however, other HCV entry factors were expressed at low levels, and none were differentially expressed in HCV-positive persons with / without fentanyl detected in their blood.DiscussionThese results highlight multiple pathways by which commonly abused opioids may affect HCV pathogenesis and may reveal additional pathways for novel target-specific therapeutic interventions and enhance the clinical management of this difficult-to-treat population.